Efficacy and safety of fecal microbiota transplantation via colonoscopy as add-on therapy in patients with mild-to-moderate ulcerative colitis: A randomized clinical trial - Tkach, Sergii; Dorofeyev, Andrii; Kuzenko, Iurii; Falalyeyeva, Tetyana; Tsyryuk, Olena; Kovalchuk, Oleksandr; Kobyliak, Nazarii; Abenavoli, Ludovico; Boccuto, Luigi (Frontiers in Medicine, 2023)
Introduction: Growing evidence supports the effectiveness of fecal microbiota transplantation (FMT) in treating ulcerative colitis (UC), although its effects seem to depend on the method of introduction, the number of procedures, the donor material, and the severity of UC. Aim: This study aimed to assess FMT’s clinical and microbiological efficacy, tolerability, and safety in patients with mild-to-moderate UC. Material and methods: Patients with mild-to-moderate UC were randomized into two groups. The first group (standard-care, n=27) was treated with basic therapy – mesalazine – at a daily dose of 3 g (2 g orally + 1 g rectally). In the second group (FMT group, n=26), while taking mesalazine at the indicated dose, each patient with UC as add-on therapy underwent a single FMT procedure with fresh material from a healthy super-donor. The clinical efficacy of treatment in both groups was evaluated after 4 and 8 weeks. The primary outcome was remission of UC, defined as a partial Mayo score ≤2, and decreased fecal calprotectin. All patients underwent bacteriological examination of feces for quantitative microbiota composition changes. Results: Clinical response in the form of a significant decrease in stool frequency and a tendency to normalize its consistency after 4 weeks was detected in 14 (51.9%) patients of the standard care group and 16 patients (61.5%) of the FMT group (p=0.583). The Mayo score in the standard care group was 3.59±1.21 and in the FMT group - 3.15±1.04 (p=0.166). After 8 weeks, the main primary endpoint was achieved in 70.4% of the standard-care group patients as compared to 84.6% of participants who received FMT as add-on therapy (p=0.215). A more pronounced decrease in Mayo score was observed in the FMT group compared to the standard-care group (1.34±1.44 vs. 2.14±1.4; p=0.045). All patients also showed a significant decrease in fecal calprotectin levels, which correlated with clinical data, stool frequency, and clinical remission. An improvement in gut microbiota composition was noted in both groups, albeit it was significantly more pronounced in the FMT group. Conclusions: FTM in patients with mild-to-moderate UC is a well-tolerated, effective, and safe method of treatment in comparison to basic therapy.